RISK FACTORS OF METABOLIC SYNDROME IN PREGNANCY INDUCED HYPERTENSION CASES - T. SUNITHA,; K.SAMEERA,; G.UMARAMANI, (International Journal of Pharma and Bio Sciences, 2012)
Hypertensive disorders complicating pregnancy are common and form great triad along with hemorrhage and infection. They are one of the important causes resulting in maternal and fetal morbidity and mortality. Metabolic syndrome is a combination of medical disorders that, when occurs together, it increases the risk of developing cardiovascular disease and diabetes. In order to know the risk of development of metabolic syndrome in women with PIH, the risk factors for metabolic syndrome like total cholesterol, HDL cholesterol, triglycerides and fasting blood sugar levels of PIH women as compared to their normotensive counterparts have been measured, analyzed and compared with earlier studies. The PIH women group exhibited highly significant increase in fasting blood sugar level, significant increase in total cholesterol and triglyceride levels and an insignificant decrease in HDL cholesterol. These results indicate that there is a significant association of abnormal lipid profiles and increased fasting blood sugar levels in PIH women.